Effects of tannin-containing diets on performance, gut disease control and health in broiler chicks - Perin G.* (2019)
© 2019 CSIRO.The emergence of antibiotic-resistant bacteria in the intestinal microbiota of broiler chickens, and the possibility of antibiotic residues in meat and meat products are seen as a threat to animal and human health. The search for alternatives to conventional drugs, including natural compounds, is an interesting approach to prevent the adverse effects of antibiotics. Therefore, the aim of the present study was to evaluate whether the addition of tannin (as a quebracho extract) in the diet of broiler chickens could be used to replace in-feed antimicrobials and coccidiostatic drugs, to exert positive effects on animal health and performance. The use of tannin in the diet of broiler chicks as an additive (at 0.5% for 1-10-day-old birds and 1.0% for 11-42-day-old broiler chickens) enhanced their bodyweight, weight gain and daily weight gain on Day 42 of life, compared with the untreated control group (P < 0.05). However, these findings were not observed when tannin was added at 0.5%. Moreover, broiler chickens fed with an extract containing tannins showed higher erythrocyte counts, as well as haemoglobin and haematocrit concentrations than did those in the control group, whereas counts of total leukocytes and lymphocytes were lower (P < 0.05). The use of a diet with tannins did not influence meat quality compared with a diet containing zinc bacitracin and salinomycin, which altered some parameters associated with meat colour. Moreover, the diet with tannins reduced (P < 0.05) the number of oocysts of Eimeria sp. (36-day-old broilers) and the total faecal bacterial counts (42-day-old broilers) compared with the control group. Finally, intestinal histopathology showed that the addition of tannins minimised the degree of lesions (Degree 1) compared with the control group (Degree 3). On the basis of these results, we concluded that the use of quebracho extract containing tannins can be a suitable approach to improve the performance of broiler chickens, replacing in-feed antibiotics and coccidiostatic drugs. The use of tannins did not change meat quality however, it caused positive effects on the immune system, and exerted potent bactericidal and coccidiostatic properties, reinforcing its use as a replacement for conventional drugs.